EFL LEARNERS` READING HABIT AND THEIR READING COMPREHENSION ENHANCEMENT THROUGH PARTNER READING - Yentri Anggeraini; Nurhasanah; Tania Madenta (Getsempena English Education Journal, 2020)
Abstract Various kinds of collaborative learning can be applied in teaching English. One of them is a partner reading strategy which allows the students to read in pairs. This research aimed at exploring the significant enhancement of partner reading strategy on the eighth-grade students` reading habit and their reading comprehension. The quasi-experimental design was used in order to gather the data and the two classes were selected through cluster random sampling as the experimental and control group. The independent sample t-test result indicated that the comparison of students` reading habit and reading comprehension in the experimental and control group with sig. (2-tailed) or p-value (0.00) was less than the alpha value (0.05). It can be concluded that the use of partner reading strategy significantly enhanced the eighth-grade students` reading habit and their reading comprehension. The partner reading strategy made the teaching and learning process more joyful and meaningful so that it can be applied as one of the activities to promote reading habit and reading comprehension.